PENGARUH PERPUSTAKAAN DIGITAL TERHADAP MINAT BELAJAR SISWA KELAS XI DI MADRASAH ALIYAH BONTOTE’NE KABUPATEN GOWA - Ardiansyah; Muhammad Nawir; Nasir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the use of a Digital Library on the learning interest of eleventh-grade students at Madrasah Aliyah Bontote'ne, Gowa Regency. This study used a one-group pretest-posttest design to measure the effect of the use of a barcode-based Digital Library on the learning interest of eleventh-grade students at Madrasah Aliyah Bontote'ne, Gowa, involving eight students. Data were collected through questionnaires and observations, and analyzed using a t-test to determine whether there was a significant increase in learning interest after the intervention. The results of the observations showed high student activity in using digital platforms, with an average of 3-4 times a week of access. Students showed high initiative and enthusiasm in searching for learning materials independently using smartphones. However, unstable internet connections and limited devices remained obstacles. In line with these observations, the learning interest questionnaire also showed a significant increase. Before the treatment, the average score obtained from the eight students was 60.88 with a total of 478, placing their learning interest in the medium to low category and indicating the need for improvement. After utilizing the digital platform, the average score jumped to 81, with a total of 648, categorized as high, and indicating a substantial increase for each student (the highest score was 89, the lowest was 85). Statistical analysis using the Paired Samples t-Test yielded a significance value of 0.000, well below the alpha threshold of 0.05. This strongly demonstrates that the difference in scores before and after the intervention is statistically significant. Although the correlation between pre- and post-treatment scores was very weak and insignificant (r = -0.045, sig. = 0.916), this substantial increase in scores strongly indicates that the implementation of the Digital Library has had a positive and tangible impact on students' learning interest.